The effects of high-altitude hypoxic environment on the pharmacokinetics and respiratory function of remimazolam: an experimental study in rats - Qingbin Chen; Li Deng; Zhen Jia (Scientific Reports)
Abstract This study investigated the impact of high-altitude hypoxic environment on the pharmacokinetics and respiratory effects of remimazolam in a rat model. Forty Sprague-Dawley rats were randomly divided into plain and plateau groups, with the plateau group exposed to a simulated altitude of 5,000 m for 72 h prior to drug administration. Pharmacokinetic parameters, respiratory function, and safety profiles were evaluated following intravenous administration of remimazolam. Results showed that high-altitude exposure significantly altered remimazolam pharmacokinetics, with increased maximum plasma concentration (1368.2 ± 227.5 vs. 1025.6 ± 184.3 ng/mL), prolonged elimination half-life (63.5 ± 10.4 vs. 48.6 ± 8.2 min), and reduced clearance (0.89 ± 0.16 vs. 1.26 ± 0.24 L/h/kg) in the plateau group compared to the plain group. The plateau group also exhibited more pronounced respiratory depression, with greater decreases in PaO₂ and oxygen saturation, and higher incidence of adverse reactions. These findings suggest that high-altitude hypoxic environment significantly impacts remimazolam pharmacokinetics and respiratory effects, necessitating careful dose adjustment and monitoring in high-altitude clinical settings.